(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
Water is an invaluable resource widely distributed in nature, it is the basis of life. Consequently, the first living cells appeared in the water environment as coacervate droplets, and in the process of evolutionary development, unicellular and multicellular organisms living in water arose from them. No living organism on earth can live without water, because the main part of its tissues is water. This article is about the protection of water resources and their effective use.